Análisis financiero de la Empresa Ferro Electric GZ - Ortega Álava, Ricardo Ronaldo (2020)
The application of a Financial analysis constitutes an important instrument of analysis within any organization because they represent a guide that will help to manage the company and also allow through Financial Indices to improve significantly, both in the management of information and an improvement in the work team. The “Ferro Electric GZ” hardware store, having ignorance of the financial information, will incur problems in both the short and long term since the administration will not have clear and timely information for making decisions quickly and accurately, making it difficult way to meet the proposed objectives. Due to the lack of knowledge of the information, the company cannot access favorable discounts that suppliers offer for canceling the cash merchandise, thus reducing the opportunities for growth in the company in addition to ignoring its debt capacity, this produces the impossibility of covering obligations to suppliers, thus generating a certain level of distrust with them. In the long term, this same ignorance could conceive of unpunctuality of certain obligations such as those contracted with financial institutions, by not complying fully, it could lead to a decrease in the level of sales due to lack of merchandise, and could even lead to suspension of payment to workers or dismissal of them. This study ensures that the hardware store knows that a financial analysis model allows the optimization of resources progressively, thus increasing the liquidity of the company, thus becoming a tool which complements the administrative management.